Melatonin, bakuchiol and ascorbyl tetraisopalmitate synergize to modulate gene expression and restore Hypoxia-Inducible Factor 1 signaling in UV-exposed skin - Narda, Mridvika; Brown, Anthony; Pérez-Cremades, Daniel; García-Giménez, José Luís; Granger, Corinne (Cellular and Molecular Biology, 2018)
Chronic exposure to solar ultraviolet (UV) radiation induces changes to the expression of hundreds of genes in the skin and modulates cellular signaling pathways that alter its structure, function and appearance. To counter these effects, we have developed a 3-in-1 night facial serum (3-in-1 NFS) comprising melatonin, bakuchiol and ascorbyl tetraisopalmitate that is designed to attenuate UV-generated free radicals and support new collagen synthesis. In order to better define its mechanism of action and gain insight into how it might influence the biology of photoaged skin, we performed a transcriptomic analysis of ex vivo skin explants that had been exposed to UV light and treated with 3-in-1 NFS each day for 4 consecutive days. Differentially expressed mRNAs and microRNAs (miRNA) were identified by RNA sequencing and a miRNA interactome was developed. Pathway enrichment analysis was performed to identify pathways likely modulated by 3-in-1 NFS. Our analysis revealed that the combination of active ingredients in 3-in-1 NFS exerted a synergistic effect on skin biology and modulated the expression of genes implicated in the regulation of collagen biosynthesis, angiogenesis, skin barrier function and cellular metabolism. Pathway analysis indicated that these events are driven by Hypoxia-Inducible Factor 1Î± (HIF-1Î±) whose expression in UV-exposed skin was partially restored upon 3-in-1 NFS treatment. To our knowledge, 3-in-1 NFS is the first non-drug demonstrated to act upon this pathway in the skin.